2015
DOI: 10.1007/s00244-015-0205-0
|View full text |Cite
|
Sign up to set email alerts
|

Essential and Toxic Elements in Blood Samples of Harbor Seals (Phoca vitulina) from the Islands Helgoland (North Sea) and Anholt (Baltic Sea): A Comparison Study with Urbanized Areas

Abstract: The harbor seals (Phoca vitulina) from Helgoland (North Sea) and Anholt (Kattegat, Baltic Sea) are top predators within the marine food web and an indicator species of the environmental contamination. Furthermore, they are a main tourist attraction. Despite these important roles, little is known about the health and pollutant contamination of these seals. The objective of this study was therefore to investigate 18 essential and nonessential/toxic elements (Al, As, Be, Ca, Cr, Cu, Fe, K, Mn, Mo, Ni, P, Pb, Rb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Furthermore, pollutant levels are still considered high enough to affect the environment and respective communities 26 . In this context, previous studies have already shown that harbour seals inhabiting the Elbe estuary have significantly higher concentrations of several trace metals in their blood compared to animals from more distant sites in the Wadden Sea or Helgoland 27 , 28 . These developments have sparked considerable conflicts between the conservation of species and the anthropogenically induced alteration of the area 29 , 30 .…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, pollutant levels are still considered high enough to affect the environment and respective communities 26 . In this context, previous studies have already shown that harbour seals inhabiting the Elbe estuary have significantly higher concentrations of several trace metals in their blood compared to animals from more distant sites in the Wadden Sea or Helgoland 27 , 28 . These developments have sparked considerable conflicts between the conservation of species and the anthropogenically induced alteration of the area 29 , 30 .…”
Section: Introductionmentioning
confidence: 87%
“…From discriminant analysis, six (dog, pig, goat, tapir, monkey, and elephant) out of 15, the species could be classied with 100% specicity. Blood samples from harbor seals (Phoca vitulina) from Helgoland (North Sea) and Anholt (Kattegat, Baltic Sea) were analysed by Kakuschke and Griesel, 364 to investigate 18 essential and nonessential potentially toxic elements using ICP-MS (Al, Be, Cr, Mn, Mo, Ni and Pb) and TXRF spectrometry (As, Ca, Cu, Fe, K, P, Rb, S, Se, Sr and Zn). Interestingly, blood concentrations of nine nonessential as well as essential trace metals (Al, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Zn) were measured to be signicantly lower in the offshore living seals from Helgoland and Anholt compared with results obtained from animals living close to urbanised areas, such as the Wadden Sea and Elbe estuary.…”
Section: Biologicalmentioning
confidence: 99%
“…Peterson et al (2015) have studied the relationship between THg levels in blood and hair in four different pinniped species. Kakuschke and Griesel as well as Hansen et al (2015) have analysed a battery of trace elements in marine mammals: in blood of harbour seals (Kakuschke and Griesel 2015) and in liver of 16 cetacean Species (Hansen et al 2015). Furthermore, although it is often very difficult to obtain feces samples of cetaceans, Lundin et al (2015) have managed to obtain and analyse feces samples of killer whales.…”
Section: Conclusion and Research Needsmentioning
confidence: 99%